Membangun kehidupan masyarakat yang damai melalui toleransi, pluralisme, dan multikulturalisme di Indonesia - Azzahra, Nadya Auliya (Maliki Interdisciplinary Journal, 2026)
Indonesia boasts immense diversity, from ethnic groups to religions, cultures, and languages. To build a peaceful and harmonious society, this diversity must be preserved. However, due to a lack of mutual respect, acts of intolerance, hatred, and social conflict are still common in the era of modern social media and technological advancements. The purpose of this essay is to explore the importance of diversity, pluralism, and tolerance in Indonesian society. This paper was written using a library research approach, utilizing various journal sources relevant to the topic discussed. The findings from the discussion demonstrate the importance of tolerance, pluralism, and diversity. These three values ​​play a role in fostering harmonious relationships between individuals and groups with different backgrounds. Furthermore, multicultural education, strengthening religious moderation, and wise use of digital media are effective strategies for instilling mutual respect and preventing the development of intolerance. Therefore, collaboration between the government, educational institutions, religious leaders, and the community is needed to strengthen the values ​​of tolerance in everyday life. Thus, Indonesia’s diversity can become a social force that supports the creation of a peaceful, inclusive, and just society.